YOUNG UNMARRIED FATHERS’ EXPERIENCES AND PERCEPTIONS OF FATHERHOOD - Makhanya, Thembelihle; Matthias, Carmel (Social Work/Maatskaplike Werk, 2018)
This article is based on a qualitative research study focusing on young unmarried fathers’ experiences and perceptions of fatherhood. Semi-structured interviews were conducted with nine fathers in KwaZulu-Natal. The participants had a total of fifteen children, four of whom lived with their fathers and paternal families. Findings indicated that high unemployment, non-payment of maintenance and cultural damages, and disputes with mothers and maternal families impacted significantly on father-child contact. All the participants wished to be more involved with their children and their conception of fatherhood extended beyond being just a provider to more nurturing roles.